Coupling halide perovskites with different materials: From doping to nanocomposites, beyond photovoltaics. (May 2020) - Righetto, Marcello; Meggiolaro, Daniele; Rizzo, Antonio; Sorrentino, Roberto; He, Zhubing; Meneghesso, Gaudenzio; Sum, Tze Chien; Gatti, Teresa; Lamberti, Francesco
Abstract: Lead halide perovskites (LHPs) have been for a decade and still remain the rising stars in current materials science research. After ten years of incessant work, researchers have reached important results in LHP photovoltaics, overcoming the 25% power conversion efficiency threshold and thus closely approaching silicon performance. On the other hand, challenges are now open for finding other useful applications for LHPs, going beyond the prevalent use in low-cost solar cell technologies. To this goal, the multiple possibilities which can be explored rely on the modification of the lattice structure of LHPs, creating libraries of different compounds with different peculiar properties. In this review, we conducted a deep and comprehensive examination of the recent literature reporting on two main strategies for making alterations at the native LHP structure. We defined them, namely, the endogenous and exogenous strategies. The first one accounts for all the compositional engineering methodologies that were applied during the last 10 years for the internal modification of the LHP lattice, while the second one refers to the realization of nanocomposites, in which LHPs and other materials are combined together. The review encompasses historic, theoretical, spectroscopic, electrical and technological contents, in order to provide a comprehensive starting point for defining a new era in LHP research.